Discovery and optimization of novel piperazines as potent inhibitors of fatty acid synthase (FASN). Issue 8 (15th April 2019) - Martin, Matthew W.; Lancia, David R.; Li, Hongbin; Schiller, Shawn E.R.; Toms, Angela V.; Wang, Zhongguo; Bair, Kenneth W.; Castro, Jennifer; Fessler, Shawn; Gotur, Deepali; Hubbs, Stephen E.; Kauffman, Goss S.; et al.
Graphical abstract: Highlights: Identified novel and potent inhibitors of FASN KR domain. Synthesis and structure activity relationships of compounds are reported. FT113 displays excellent cellular activity and pharmacokinetic properties. FT113 is a valuable tool to develop POC models of DNL driven disease. Abstract: The discovery, structure-activity relationships, and optimization of a novel class of fatty acid synthase (FASN) inhibitors is reported. High throughput screening identified a series of substituted piperazines with structural features that enable interactions with many of the potency-driving regions of the FASN KR domain binding site. Derived from this series was FT113, a compound with potent biochemical and cellular activity, which translated into excellent activity in in vivo models.